Tawakal: Status Hadis dan Pandangan Ulama - Rustan Rustan (DIALEKTIKA, 2021)
The understanding of tawakal shows something that makes the meaning of tawakal different in each scholar. Some identify tawakal only as an absolute surrender that can make a person not try and strive. In line with that, this paper in addition to mapping the views of the scholars on the authenticity of the hadith tawakal, also analyse the meaning of the hadith by the scholars and see the comparisons that exist. This paper is based on data collected from a literature study by selecting hadiths that are relevant to the discussion in this paper. The results of this paper prove that scholars give reviews on tawakkal in various ways. This is driven by their understanding of the authenticity of the hadith used as a reference.Keywords: Tawakal, Hadis, The Scholars Viewpoint